Architectural representation in medieval textual and material culture - Bailey, Hannah McKendrick,Kinsella, Karl,Thomas, Daniel (Arc Humanities Press, 2023)
Exploring the work of writers, illuminators, and craftspeople, this volume demonstrates the pervasive nature of architecture as a category of medieval thought. The architectural remnants of the past - from castles and cathedrals to the lowliest village church - provide many people with their first point of contact with the medieval period and its culture. Such concrete survivals provide a direct link to both the material experience of medieval people and the ideological and imaginative worldview which framed their lives. The studies collected in this volume show how attention to architectural representation can contribute to our understanding of not only the history of architectural thought but also the history of art, the intersection between textual and material culture, and the medieval experience of space and place.
Keywords: Aufsatzsammlung; Architektur; Architekturbild; Architekturzeichnung; Literatur; Sachkultur; Mittelalter; Architecture; Medieval; in literature; Architecture; Medieval; in art; Architecture; Medieval